An Analysis of English Textbook Focusing on Reading Material to Enhance Students’ Critical Thinking in Recount Text and Narrative Text (RETAIN, 2020)
Abstract Reading is one of the important that must be mastered by students in Indonesia, especially students who are learning English. To make students master English reading material, they need good quality reading material so that they can also improve their critical thinking skills in reading English texts. The purpose of this study is to spot textbooks that concentrate on reading material about recount text and narrative text to enhance students' critical thinking skills. This study is a document analysis by analyzing an English textbook for tenth grader students titled “Bahasa Inggris” written by Utami Widiat et al. published by the Ministry of Education and Culture 2013 Curriculum as a data source. From the results in this study, the researcher concludes an English textbook consisting of fifteen parts, and every part has its topic and material. The chapters that have been selected by researchers about the recount text and narrative text in chapters 8, 9, 10, 11, 12, 13, 14 in English textbooks are all themes and materials according to the basic competencies 3.7, 4.7 and 3.8, 4.8 are accordance in the 2013 curriculum and can also improve students' critical thinking skills. Some suggestions are given to the authors, teachers, and subsequent researchers to look for further sources and provide more useful results from the textbook analysis. Keywords: textbook analysis, reading, critical thinking.